Mengembangkan Kemampuan Berpikir Spasial Melalui Pendidikan STEM di Sekolah Dasar: Developing Spatial Thinking Abilities Through Stem Education In Elementary Schools - Lokollo, Lamberthus J.; Lasaiba, Mohammad; Arfa, Arman Man; Lasaiba, Djamila (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This study explores the effectiveness of STEM education in developing spatial thinking skills in elementary school students. The study employs a quasi-experimental design involving two groups: an experimental group that received STEM intervention and a control group following the standard curriculum. The results indicate that the experimental group experienced significant improvements in visualization, spatial relationship understanding, and spatial object manipulation compared to the control group. These improvements are primarily to technology, such as 3D simulations and design software, which help students comprehend complex spatial concepts. Further statistical analysis supports these findings, showing significant differences between the experimental and control groups. These findings underscore the importance of integrating STEM education into the curriculum to enhance students' spatial skills, which are critical in various science and technology disciplines. However, challenges in implementation, such as a need for more resources and teacher training, must be addressed to ensure the program's effectiveness across different educational contexts.